2021
DOI: 10.3390/ijerph182010732
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Socioecological Determinants of Hong Kong Workers’ Work-Life Balance: A Grounded Theory Model

Abstract: Background: Although a growing body of research has investigated the theoretical and empirical models of work-life balance (WLB), the propositions of this phenomenon remain nonunified. Thus, a grounded theory approach was adopted to explore the viewpoints of workers regarding WLB and its determinants and consequences. Methods: Individual face-to-face interviews were conducted to investigate the attitudes and experiences of Hong Kong workers towards WLB, in which 50 workers were interviewed. All data of intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Discrimination and stigmatization [44,84], apathy [44], fears, and self-scrutiny/judgment [44,61,62] are barriers to achieving a healthy work-life balance. Moreover, in the local context of Hong Kong, the prevalent concept of "work-life separation"-that personal matters should not be imposed on the workplace-hinders a healthy work-life balance [86]. While more flexible and permeable boundaries are associated with work-life enhancement [87], Hong Kong's prevailing corporate culture generally appears quite the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination and stigmatization [44,84], apathy [44], fears, and self-scrutiny/judgment [44,61,62] are barriers to achieving a healthy work-life balance. Moreover, in the local context of Hong Kong, the prevalent concept of "work-life separation"-that personal matters should not be imposed on the workplace-hinders a healthy work-life balance [86]. While more flexible and permeable boundaries are associated with work-life enhancement [87], Hong Kong's prevailing corporate culture generally appears quite the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the associations between satisfaction with work-life balance and stress in balancing work and life through several demographic factors among dual-career families in Hong Kong. Previous studies revealed that most workers prefer more flexible working hours rather than material returns [47]. With a view to creating a more conducive environment for work-life balance, proactive steps should be taken to encourage employers to develop flexible employment practices and working conditions for employees.…”
Section: Discussionmentioning
confidence: 99%